Service Innovation of Nakaza Tour on Customer Satisfaction - Ahmad Rafi kurniawan; Heru Suheryadi; Imas Masriah (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Purpose: This study aims to examine the effect of service innovation on customer satisfaction in the context of Nakaza Tour. Specifically, the research investigates how different aspects of service innovation such as digital technology usage, ease of access to information, and improvements in service delivery contribute to perceived service quality and ultimately affect customer satisfaction. Methods: The study adopts a descriptive quantitative approach. Data were collected from 100 customers who had used Nakaza Tour services within the past six months, using structured questionnaires and interviews. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS software to measure both direct and indirect relationships among the variables: Service Innovation (independent), Service Quality (mediating), and Customer Satisfaction (dependent). The SERVQUAL model was applied to assess service quality dimensions, while the Innovation Diffusion Theory provided a theoretical basis for understanding customer adoption of service innovations. Conlusion: The results indicate that service innovation has a significant positive impact on both service quality and customer satisfaction. Specifically, service innovations such as personalized travel packages, responsive online booking systems, and active communication via digital platforms significantly enhance service quality perceptions. Furthermore, service quality plays a mediating role in strengthening the impact of innovation on satisfaction. The SEM model explains 64% of the variance in customer satisfaction and reveals a total effect of 0.77 for service innovation.